Japanese Sounding Rocket Programme at Syowa Station, Antarctica (Reports of the Japanese Antarctic Research Expedition) - Masayoshi MURAYAMA; Kou KUSUNOKI; Sadao KAWAGUCHI (National Institute of Polar Research, 1972)
The programme of the use of sounding rockets at Syowa Station in Antarctica was proposed by the National Antarctic Committee of the Science Council of Japan. The Polar Research Center, National Science Museum, has taken the responsibility for detailed planning, co-operated by other organizations concerned. The programme has been officially approved by the Promoting Headquarters of the Japanese Antarctic Research Expedition under the direction of the Minister of Education. The rocket range at Syowa Station was inaugurated in January 1969, erecting three buildings, namely, a control centre, a telemetry station, and a rocket assembly shop. Two kinds of rockets, S-160 (peak altitude about 90km) and S-210 (about 120km), were selected to be used in the initial stage of the research programme. In January 1970, a launcher was connected with the assembly shop and necessary equipment was installed for the first test launching of S-160. In February 1970, two test flights for measuring electron density and ozone concentration were successfully accomplished, reaching to an altitude of about 90 km. Future programme of launching six S-210 and one S-160 in the austral winter of 1971 and 1972 is described.